Peripheral lymphadenopathy of unknown origin in adults: a diagnostic approach emphasizing the malignancy hypothesis (Swiss Medical Weekly, 2024)
The term lymphadenopathy refers to an abnormality in size, consistency or morphological aspect of one or several lymph nodes. Although lymphadenopathies are commonly observed in everyday clinical practice, the difficulty of differentiating benign and malignant disease may delay therapeutic approaches. The present review aims to update diagnostic algorithms in different clinical situations based on the currently available literature.A literature review was performed to assess current knowledge of and to update the diagnostic approach. A short clinical vignette was used as an example of a typical clinical presentation. This case of metastatic lymphadenopathy with incomplete patient history demonstrates how misleading such lymphadenopathy may be, leading to a delayed diagnosis and even a fatal outcome.Any lymphadenopathy persisting for more than 2 weeks should be considered suspicious and deserves further investigation. Precise clinical examination, meticulous history-taking and a search for associated symptomatology are still cornerstones for diagnosing the origin of the condition. The next diagnostic step depends on the anatomical region and the specific patient’s situation. Imaging starts with ultrasound, while computed tomography (CT) and magnetic resonance imaging (MRI) allow assessment of the surrounding structures. If the diagnosis remains uncertain, tissue sampling and histological analyses should be performed.Except for head and neck loco-regional lymphadenopathy, there are no methodical guidelines for persistent lymphadenopathy. The present review clarifies several confusing and complex situations. The accuracy of fine needle aspiration cytology could be increased by using core needle biopsy with immunocytologic and flow cytometric methods. Notably, except in the head and neck area, open biopsy remains the best option when lymphoma is suspected or when inconclusive results of previous fine needle aspiration cytology or core needle biopsy are obtained. The incidence of malignant lymphadenopathy varies with its location and the various diagnostic strategies. In metastatic lymphadenopathy of unknown primary origin, European Society for Medical Oncology (ESMO) guidelines and modern methods like next-generation sequencing (NGS) may help to manage such complex cases.